Pre‐clinical development of a blood‐brain barrier (BBB)‐penetrating anti‐amyloid‒β fusion protein: Nonhuman/Target identification and validation studies: Amyloid. (7th December 2020) - Chakravarthy, Balu; Comas, Rosa; Atkinson, Trevor; Menard, Michel; Brunette, Eric; Jiang, Susan; Haukenfrers, Julie; Charlebois, Claudie; Delaney, Christie; Dudani, Renu; Aylsworth, Amy; Tauskela, Joseph; et al.
Abstract: Background: We have developed a blood‐brain barrier (BBB) crossing anti‐amyloid fusion protein KG207 as a potential AD therapeutic. This humanized bi‐functional molecule was generated by fusing an Aß oligomer (AßO)‐ binding peptide (ABP) with a BBB carrier FC5 via IgG‐1 Fc fragment. Present study shows that KG207 crosses the BBB in vitro and in vivo (mouse, rat and dog), penetrates target regions of the brain (cortex and hippocampus) and engages parenchymal Aß. KG207 neutralizes AßO‐induced toxicity in vitro and does not stimulate pro‐inflammatory cytokine production in mouse microglia. Studies demonstrated that KG207 was safe up to 300 mg/kg. Method: Recombinant KG207 was produced in CHO cells. BBB‐permeability was assessed using in vitro BBB (formed by rat or human brain endothelial cells) and in vivo (rat, mouse and dog) models. AßO binding was determined by ELISA. Following iv injection, serum, CSF and brain levels of KG207 and Aß were assessed by nanoLC‐ MRM, ELISA and Western blot methods. Aß toxicity studies were done in human neuroblastoma (SH‐SY5Y) cells and rat primary cortical neuronal cells. Following exposure to KG207, cytokine levels in BV2 microglia were measured using Millipore Luminex assay kit. Safety studies were done in Sprague Dawley rats at 30, 100 and 300 mg/kg. Result: KG207 retained both Aß‐oligomer binding activity and BBB‐permeability in vitro . When injected iv into rats and mouse, KG207 rapidly appeared in the CSF and brain parenchyma (cortex and hippocampus) indicating active transport of ABP across BBB by FC5 in vivo . In AD transgenic mice, KG207 treatment showed a significant reduction of brain Aß levels. KG207 significantly reduced AßO‐induced toxicity in both human neuroblastoma cells and primary cortical neurons in vitro . KG207 blocked AßO binding to cellular proteins in vitro . KG207 did not activate BV2 mouse microglia and induce pro‐inflammatory cytokines. No adverse effects were seen in rats injected with up to 300 mg/kg, including neurotoxicity. Conclusion: Collectively, these results indicate that KG207 can effectivey cross the blood‐brain barrier, penetrate the brain and facilitate Aß clearance in vivo . In vitro data suggest that KG207 can safely clear Aß without eliciting pro‐inflammatory cytokine secretion by microglia.